Regulation on Shariah Compliance For Hospital In Indonesia - Hosen, H M Nadratuzzaman (International Journal of Human and Health Sciences (IJHHS), 2024)
The National Sharia Council-Indonesian Ulema Council (DSN-MUI) is an independent institution which was formed to realize the aspirations of Muslims regarding issues related to the economy. Through the vision of making sharia economics more common and sharia-compliant in the community's economy, DSN MUI has issued various fatwas based on the request of the community, including guidelines regarding the implementation of sharia hospitals. The guideline for administering sharia hospitals was issued based on a fatwa request from the All-Indonesian Islamic Health Effort Council (Mukisi) in 2015 regarding the importance of managing hospitals in Indonesia in accordance with sharia principles, namely in maintain of Religion (khifdz ad-din), nurturing the Soul (khifdz an-nafs), caring for offspring (khifdz an-nasl), maintaining Intellect (khifdz al-aql), maintaining assets (khifdz al-mal). Therefore, based on the results of the study and considerations of experts, the fatwa was arranged and issued by DSN MUI Number of 107/DSN-MUI/IX/2016 concerning guidelines for administering sharia hospitals based on sharia principles. The implementation of a Sharia Hospital is very important for all elements related to hospital maintenance activities, including for patients and the hospital, for hospitals and the suppliers, such as laboratories, medicine, and other facility providers. The interests for patients, among others, are that the implementation of a Sharia Hospital will be able to provide for the patient's spiritual needs during illness or at the end of the patient's life, maintain patient privacy, patients receive quality services, and patients will receive blessings because they are protected by providing halal, healthy food and protecting the environment, as well as a clear agreement on patient care in accordance with sharia contracts. Apart from that, it is of interest for hospital management in general, that the hospital will carry out business in accordance with Islamic law and in its management, the Hospital will avoid prohibited sharia transactions, namely usury, rishwah and gharar. Furthermore, for standardized certification for the implementation of sharia hospital, MUKISI has prepared management and service guidelines which are arranged in the standard book and sharia hospital instruments version 1441. There are 12 assessment standards consisting of 62 standards and 201 assessment elements which are in accordance with the fatwa MUI. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S29